Textiles. Quantitative chemical analysis. Mixtures of acrylic, certain modacrylics, certain chlorofibres, certain elastane fibres with certain other fibres (method using dimethylformamide) Part 12, (27th October 2020) - British Standards Institution,
No abstract available